2008
DOI: 10.1097/ico.0b013e3181605ff9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Experimental Angiogenesis of Cornea by Various Doses of Doxycycline and Combination of Triamcinolone Acetonide With Low-molecular-weight Heparin and Doxycycline

Abstract: Topically administered combinations of triamcinolone acetonide plus LMWH or triamcinolone acetonide plus doxycycline had effects that contributed to efficient suppression of corneal neovascularization; these drugs were ineffective at similar concentrations used alone. Topically administered 2% (pH neutralized) doxycycline has antiangiogenic effects, which contributed to significant suppression on corneal neovascularization. This drug may be therapeutically beneficial in treatment of corneal neovascularization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 39 publications
1
20
1
4
Order By: Relevance
“…Our study further supported the existing data showing that doxycycline could inhibit corneal NV [24,25]. Furthermore, our study showed that the ideal concentration of doxycycline to inhibit rats corneal NV might be 0.05% and 0.1%.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study further supported the existing data showing that doxycycline could inhibit corneal NV [24,25]. Furthermore, our study showed that the ideal concentration of doxycycline to inhibit rats corneal NV might be 0.05% and 0.1%.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our study showed that the ideal concentration of doxycycline to inhibit rats corneal NV might be 0.05% and 0.1%. This was different from what Sanders and others reported that 2% topical doxycycline neutralized solution was the recommendation for the treatment of corneal NV [25]. Two factors may cause this difference.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Уже тогда было замечено положительное влияние препарата на микроцир-куляцию, способность к регенерации тканей, его противоотечный эффект [10]. А в сочетании с ГКС, доксициклином или аргон-лазерной коагуляцией гепарин уменьшал рост новообразованных сосудов роговицы [7,33,34,37,51]. Несмотря на то, что в общей медицине гепарин известен, прежде всего, как прямой антикоагулянт, его биологическая роль намного шире.…”
unclassified